Chains, Shops and Networks: Official Statistics and the Creation of Public Value - Asle Rolland (Statistika: Statistics and Economy Journal, 2015)
The paper concerns offi cial statistics, particularly as produced by the NSIs. Their contribution to the society is considered well captured by the concept of public value. Official statistics create value for the democracy as foundation for evidence-based politics. Democracies and autocracies alike need statistics to govern the public. Unique for the democracy is the need of statistics to govern the governors, for which the independence of the NSI is crucial. Three ways of creating public value are the value chain, the value shop and the value network. The chain is appropriate for the production, the shop for the interpretation and the network for the dissemination of statistics. Automation reduces the need to rely on the value chain as core business model. Thereto automation increases the statistical output, which in turn increases the need of shop and network activities. Replacing the chain with the shop as core model will elevate the NSIs from commodity producers to a processing industry.